Implementation Of Anticipatory Guidance On Mothers' Knowledge And Attitudes In Preventing Accidents In Preschool Children - Rika Maya Sari; Naylil Mawadda Rohma; Saiful Nurhidayat; Nova Ardhita Putri (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Preschool aged children will begin to be interested in speed and movement, with increased involvement in outdoor activities, children can strive to develop skills, perform gross motor activities carefully without fear, and experience the joy of trying new things., mobility leads on increasing independence. Activities outside the home can pose a risk of possible injury at this age, such as motor vehicle accidents, drowning, burns, poisoning, and personal injury. This study was conducted with the aim of determining the extent of the influence of anticipatory guidance on mothers' knowledge and attitudes in preventing accidents in preschool-aged children at BA Aisyiyah Ronowijayan, Siman, Ponorogo. Method: The design used in this study was a pre-experiment with a one group pre-post test approach, with a total sample of 34 parents. of BA Aisyiyah Ronowijayan students, with purposive sampling. Result: The research results are based on the Wilcoxon Sign Rank Test and the McNemar Sign Rank Test. The results of the study showed that there was an influence of anticipatory guidance based on video media on the level of knowledge of parents in preventing injuries to pre-school children (p=0.000). It was found that there was an influence of providing health education using video media in the form of anticipatory guidance on parents' attitudes in preventing injuries in preschool-aged children. (p=0.000). Conclusion: Video media has proven effective in increasing parents' knowledge and attitudes. It is hoped that this video can be applied in everyday life.